Analisis Nilai Karakter Wayang Punakawan sebagai Media Pembelajaran Bahasa Jawa di SD - Zuhriah, Amillatuz; Nur'aini, Hepy Dwi; Firmansyah, Muhammad Rizky; Putri Aji, Jiva Laelatul Fitri; Zulaili, Iin Nur (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
This research aims to analyze the character values of the Punakawan wayang which then becomes a consideration for its use as a learning medium in Javanese language subjects in elementary schools. This research uses qualitative methods which are then analyzed using descriptive analysis. The results of the discussion from this research are that the use of stories from the Punakawan wayang as a learning medium will have a positive impact if the teacher can highlight the good character values of the wayang which can be emulated by students, and vice versa